PRT062607 Achieves Complete Inhibition of the Spleen Tyrosine Kinase at Tolerated Exposures Following Oral Dosing in Healthy Volunteers. (17th August 2016) - Coffey, Greg; Rani, Aradhana; Betz, Andreas; Pak, Yvonne; Haberstock‐Debic, Helena; Pandey, Anjali; Hollenbach, Stanley; Gretler, Daniel D.; Mant, Tim; Jurcevic, Stipo; Sinha, Uma
Abstract: The spleen tyrosine kinase (SYK) regulates immune cell activation in response to engagement of a variety of receptors, making it an intriguing target for the treatment of inflammatory and autoimmune disorders as well as certain B‐cell malignancies. We have previously reported on the discovery and preclinical characterization of PRT062607, a potent and highly selective inhibitor of SYK that exhibits robust anti‐inflammatory activity in a variety of animal models. Here we present data from our first human studies aimed at characterizing the pharmacokinetics (PK), pharmacodynamics (PD), and safety of PRT062607 in healthy volunteers following single and multiple oral administrations. PRT062607 demonstrated a favorable PK profile and the ability to completely inhibit SYK activity in multiple whole‐blood assays. The PD half‐life in the more sensitive assays was approximately 24 hours and returned to predose levels by 72 hours. Selectivity for SYK was observed at all dose levels tested. Analysis of the PK/PD relationship indicated an IC50 of 324 nM for inhibition of B‐cell antigen receptor‐mediated B‐cell activation and 205 nM for inhibition of FcεRI‐mediated basophil degranulation. PRT062607 was safe and well tolerated across the entire range of doses. Clinical PK/PD was related to in vivo anti‐inflammatory activity of PRT062607 in the rat collagen‐induced arthritis model, which predicts that therapeutic concentrations may be safely achieved in humans for the treatment of autoimmune disease. PRT062607 has a desirable PK profile and is capable of safely, potently, and selectively suppressing SYK kinase function in humans following once‐daily oral dosing.